René Van Huffel, un privilegiado puente con la cultura de habla francesa - Valembois, Víctor (2011)
I never met him in person, but his picture in the Gallery of Emeritus Professor at the School of Education called my attention due to his typical Belgian name. I started searching for information about him and his life to construct a kind of biography. This incomplete and modest reconstruction of his accomplishments shows a model of language teaching. It is also an example for the concept of university in times of globalization, well understood to intercultural interferences and the philological connotation: I hope that this reconstruction, not hagiographic but deeply humanistic, serves both as a rescue effort considering the past and as a useful tool while looking into the future.